2020
DOI: 10.1108/ara-05-2019-0112
|View full text |Cite
|
Sign up to set email alerts
|

Earnings persistence, institutional investors monitoring and types of political connections

Abstract: PurposeThe purpose of this study is to examine whether institutional investors monitoring attenuate (exacerbate) weaker earnings persistence in politically connected firms (PCFs). In addition, it investigates whether earnings persistence do vary according to different types of political connections.Design/methodology/approachThis study employs earnings persistence as measure of earnings quality and ordinary least squares (OLS) model to examine: (1) the moderating effect of institutional investors’ ownership on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Second, this study offers empirical evidence of forecast accuracy and dispersion to address the lack of studies examining forecast variables in Malaysia. A recent work by Tee and Rasiah (2020) found that strong earnings persistence was associated with PCON firms that had established political ties, and our results provided further validation of this by using different proxies for earnings quality. We focused on analysts' behaviors—specifically, their ability to make accurate earnings forecasts—because analysts play important roles as information intermediaries in global capital markets, reducing the information asymmetry between management and investors.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Second, this study offers empirical evidence of forecast accuracy and dispersion to address the lack of studies examining forecast variables in Malaysia. A recent work by Tee and Rasiah (2020) found that strong earnings persistence was associated with PCON firms that had established political ties, and our results provided further validation of this by using different proxies for earnings quality. We focused on analysts' behaviors—specifically, their ability to make accurate earnings forecasts—because analysts play important roles as information intermediaries in global capital markets, reducing the information asymmetry between management and investors.…”
Section: Introductionsupporting
confidence: 84%
“…The results indicated that PCON firms with established political ties had stronger earnings persistence due to the fact that they were efficient and profitable in the long term, hence increasing their reputation and prestige. These results showed that PCON firms should not be treated as an analytically homogenous group of firms (Tee and Rasiah, 2020). In other words, it is necessary to examine different types of PCON firms to provide insights into their effect on various accounting and finance measurements.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In Malaysia, the effectiveness of institutional investors as monitoring bodies has been recognised in previous studies. For example, the existence of institutional investor leads to improved earnings quality (Abdul Jalil & Abdul Rahman, 2010;Tee & Rasiah, 2020), improved stock price informativeness (Tee, 2017), lower risk of stock price crashes (Tee, 2019;Tee, Yee et al, 2018), attenuated cost of debt (Tee, 2018), demand for higher audit quality (Tee et al, 2017), and is associated with higher dividend payouts (Benjamin et al, 2016) which indicate effective monitoring. Therefore, sell-side analysts as information intermediaries should issue more favourable stock recommendations for the companies with higher institutional investor ownership.…”
Section: Sell-side Analysts Stock Recommendations and Institutional Investors' Ownershipmentioning
confidence: 99%